Social Media Specialist & Strategi Pemasaran PT. Telkom Landmark Tower Surabaya - Kristanti, Kartika; Kusuma, Yanda Bara (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to determine the target market of PT. Telkom Indonesia Tbk in increasing sales of roaming data packages. The research method used in this research is qualitative research, namely literature study and field research. Where the data collection system in this research comes from journals which are analyzed in the form of explanations in the form of information originating from within and outside agencies related to the sale of PT roaming data packages. Telkom Indonesia Tbk Surabaya City. The research results show that in increasing sales of roaming data packages PT. Telkom Indonesia Tbk Surabaya City uses marketing strategies in the form of Direct Selling and Direct Selling Digital, the target markets are individual customers, corporate customers, tourist customers, global business customers and event conference customers.